Letter Writing: A Creative Tool for School Counselors Working with Adolescents. Issue 3 (3rd July 2018) - DeCino, Daniel A.; Waalkes, Phillip L.; Smith, Paul
ABSTRACT: Letter writing is a therapeutic tool used in many helping professions with many populations. In school counseling, letter writing can be a useful way for school counselors to build relationships and assess student needs. Letter writing may appeal to students who are more introspective and prefer less direct forms of communication (France, Cadieax, & Allen, 1995). Evidence to support school counselors' use of letter writing with students is underdeveloped. Citing conceptual, empirical, and theoretical support, the authors propose prompting students to write Letters About Themselves (LAT) at the beginning, middle, and end phases of the school year. Considerations for school counselors using letter writing with adolescents are explored.